Identifying Accurate Internet Resources for Nutrition, Food Safety, and Health Demonstrations - Amy Simonne; Linda B. Bobroff (EDIS)
FCS-8797, a 4-page fact sheet by Amy Simonne and Linda B. Bobroff, aims to assist 4-H county faculty and volunteers in directing youth to accurate, research-based sources of information on nutrition, food safety, and health. Published by the UF Department of Family Youth and Community Sciences, October 2006. (Also included in the 4-H and Youth New Publications mailing).